2006
DOI: 10.1074/jbc.m602480200
|View full text |Cite
|
Sign up to set email alerts
|

ATP-consuming and ATP-generating Enzymes Secreted by Pancreas

Abstract: Pancreatic acini release ATP in response to various stimuli, including cholecystokinin octapeptide (CCK-8), as we show in the present study. There were indications that pancreatic juice also contains enzymes that could hydrolyze ATP during its passage through the ductal system. The aim of this study was to determine which ATP-degrading and possibly ATP-generating enzymes were present in pancreatic secretion. For this purpose, pancreatic juice was collected from anesthetized rats stimulated with infusion of CCK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 36 publications
4
60
0
Order By: Relevance
“…However, one should recall that we monitor ATP concentrations that depend on a balance between ATP release and ATP hydrolysis. In pancreatic acini, agonists and hormones also stimulate release/activation of ecto-nucleotidases (CD39 and CD73) that contribute to rapid breakdown of ATP [5,7]. Whether mechanical stimuli bypass these processes in acini is not clear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, one should recall that we monitor ATP concentrations that depend on a balance between ATP release and ATP hydrolysis. In pancreatic acini, agonists and hormones also stimulate release/activation of ecto-nucleotidases (CD39 and CD73) that contribute to rapid breakdown of ATP [5,7]. Whether mechanical stimuli bypass these processes in acini is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…ATP is released from most cells, and the release mechanism is currently an intensive research field, where the focus is on identifying whether ATP is released via ion channels/ transporters, pannexin or connexins, or via vesicular transport [2,3]. In the exocrine pancreas, it has been well documented that acini release ATP in response to physiological signals, such as cholinergic agonists, cholecystokinin, and neurotensin [4][5][6]. Acinar cells also secrete digestive enzymes and nucleotideconverting enzymes [5,7], and our earlier studies indicated that zymogen granules and fluorescent markers for ATP stores are co-localized [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that catalytically active NTPDase1 can be shed in membrane-bound form from plasma membranes of NTPDase1-expressing cells. The hydrophobic form of NTPDase1 has been found in particulate secretions of rat pancreas under resting conditions [155] and as a result of stimulation with cholecystokininoctapeptide-8 where it is thought to regulate intraluminal ATP concentrations within the ductal tree [129,156]. However, ecto-ATPase appears to be absent from guinea pig and human pancreatic secretions, implicating species-specific differences [157].…”
Section: Soluble Formsmentioning
confidence: 99%
“…It can also be released into pancreatic juice [156]. Binding of monoclonal antibodies to lymphocyte eN but not to endothelial eN caused shedding of the protein [249].…”
Section: Soluble Formsmentioning
confidence: 99%